About principles of legal regulation limitations in the implementation of the economic activities of agricultural producers - Коломієць, Я. Л. (Theory and practice of jurisprudence, 2016)
In the article the principles of legal regulation in the sphere of restrictions on industrial and economical activity of agricultural commodity producers are formulated. Among these principles is primarily the principle of optimal harmonizing of public and private interests while imposing restrictions on fulfilling of industrial and economical activity of agricultural commodity producers. Only the balance between public and private interests under imposing the specified restrictions enables various subjects to achieve their respective aims while realizing industrial and economical activity. Another principle applied under establishing restrictions on industrial and economical activities of agricultural commodity producers is the principle of legality. Restrictions such as prohibitions, terms and obligations are determined by legal rules and embodied in the respective legislative acts. As they are worded in rules of law such legislative prescriptions are binding upon all participants of agricultural legal relationships among which agricultural commodity producers have a significant place. Under establishing restrictions on fulfillment of industrial and economical activities of agricultural commodity producers the principle of the priority of the environmental safety requirements is of great importance. Such requirements under fulfillment of industrial and economical activities by agricultural commodity producers must take priority, since it concerns the protection of life and health of an individual. In the case of abridgement of agricultural commodity producers’ rights to carry out their activities connected with output of agricultural commodity, processing of domestic manufacture output and sales of products first of all it is necessary to secure the respective public interests. These interests lie in the necessity for ensuring safety and quality of output. The given restrictions are imposed on a pro rata basis with regard to agricultural commodity producers having the same legal status (agricultural enterprises or entrepreneurs, specialized agricultural enterprise) or carrying out the same kind of industrial and economical activity (in the crop production or animal breeding). Therefore the principle of symmetry (commensurability) in the case of imposing restrictions on carrying out industrial and economical activity of agricultural commodity producers was distinguished. Key words: industrial and economical activity, the principles of agricultural law, restrictions on carrying out economical activity, agricultural commodity producers.